International Institutions and Strategies of European Countries after the Cold War (Czech Journal of International Relations, 1994)
After ther Cold War. lnternational lnstitutions and State Strategies in Europe, 1989-1991. Edited by Robert O. Keohane, ]oseph S. Nye, Stanley Hoffmann. Harvard University Press, Cambridge, Massachusetts and London, England 1993, 481 stran, ISBN 0-674-00863-4.